2018
DOI: 10.1002/ejlt.201800150
|View full text |Cite
|
Sign up to set email alerts
|

Improving Quality Preservation of Raw Peanuts Stored under Different Conditions During a Long‐Term Storage

Abstract: This research evaluated the chemical, microbiological, and sensory quality preservation of raw peanuts packed in high barrier ethylene vinyl alcohol bags (EVOH) under vacuum and in polypropylene (PP) bags, during 720 days of storage at 10° (T10) and 25 °C (T25). Peroxides (PV) and conjugated dienes (CD) remained almost stable in EVOH at 10 °C (EVOH‐T10). The free fatty acid increase was greater in peanuts packaged in EVOH at 25 °C than at 10 °C. EVOH‐T10 presented the lowest saturated/unsaturated and oleic/lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 38 publications
1
17
3
Order By: Relevance
“…In contrast to the current findings, Martín et al. () found that this volatile compound showed decreases during storage were affected by the type of packaging, temperature, and storage time. Nevertheless, peanut samples used in that research were subjected to a markedly longer term storage with respect to the current work.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to the current findings, Martín et al. () found that this volatile compound showed decreases during storage were affected by the type of packaging, temperature, and storage time. Nevertheless, peanut samples used in that research were subjected to a markedly longer term storage with respect to the current work.…”
Section: Resultscontrasting
confidence: 99%
“…Decane-5,6-bis(2,2-dimethylpropilidene)-(E,Z)-remained, in general, constant for all treatments throughout the entire storage without significant differences between them. Past studies also found this volatile compound in peanuts and other legumes (Martín et al, 2018a;Moniruzzaman, Shahinuzzaman, Haque, Khatun, & Yaakob, 2015). In contrast to the current findings, Martín et al (2018a) found that this volatile compound showed decreases during storage were affected by the type of packaging, temperature, and storage time.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…It can be seen from Fig. 6 that the VE content of peanut dried by solar radiation was 104.9 40 also demonstrated the effectiveness of oxygen isolation and low temperature environment in protecting the quality of tocopherols.…”
Section: Physical Physiological and Chemical Characteristicsmentioning
confidence: 75%